The Mindfulness- Based Soccer Program (MBSoccerP): Effects on Elite Athletes - Carraça, Bruno; Serpa, Sidonio; Rosado, Antonio; Palmi, Joan (Cuadernos de Psicología del Deporte, 2018)
Newly, 3º wave CBT programs suggest that mindfulness-based programs might be an powerful strategy to optimize performance and improve flow. The aim of this study was to examine the effectiveness of a mindfulness-based soccer program (MBSoccerP) on elite soccer athletes. In a quasi-experimental design with experimental (n = 28) and control group (n = 29), the effectiveness of MBSoccerP was tested. The results of an analysis of covariance with repeated measures indicate that the intervention group (M=25.68, SD=3.42) significantly improved in FFMQ_Act awareness, FFMQ_Non react, SCS_Mindfulness, SCS_Self-Kindness, SCS_Common-Humanity, DFS2_total, and decreased BSI_Anxiety and AAQ-II, as traits compared to the control group, and increase direct measures scores of sport performance FAIP-A_global and FAIP-T_global performance. Results suggest that MBSoccerP can be effective in enhance elite soccer performance, self-compassion, psychological flexibility, mindfulness and flow.